Live Car Lane and Traffic Detection (Using Machine Learning) - Vyankatrao Patle, Sapna; Milind Gotekar, Srushti; Gyanrao Mahale, Sakshi; Basant Sahare, Aakansha; Warjurkar, Sarvesh (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Lately numerous innovative progressions are coming in the area of street security as mishaps has been expanding at a disturbing rate and one of the urgent justification such mishaps is absence of driver's consideration. Specialized progressions ought to be there to lessen the recurrence of the mishaps and stay safe. One of the approaches to do this is through path discovery frameworks that work with the expectation of perceive the constraints of the path out and about and driver on the off chance that he changes and goes to wrong path markings. The path location framework is a fundamental segment of numerous mechanically savvy transport framework. Despite the fact that it is an intricate objective to accomplish because of the glinting street conditions that an individual meets particularly while driving around evening time or even in the light of day. Path limits are identified utilizing a camera that catches the perspective out and about, mounted before the vehicle. The methodology utilized in this article changes the picture removes video into a bunch of sub pictures and creates picture qualities for every one of them which are then used to recognize the tracks present on the streets.
Keywords: Traffic Safety; Lane Detection; Deep Learning; Computer Vision